Synthesis, spectral and thermal studies on pyrazolate-bridged palladium(II) coordination polymers - Netto, Adelino Vieira de Godoy [UNESP]; Frem, Regina Célia Galvão [UNESP]; Mauro, Antonio Eduardo [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Zorel, H. E. (Springer, 2007)
Synthesis, spectroscopic characterization and thermal behavior of pyrazolate-bridged palladium complexes [Pd(mu-Pz)(2)](n) (1), [Pd(mu-mPz)(2)](n) (2), [Pd(mu-dmPz)(2)](n) (3), [Pd(mu-IPz)(2)](n) (4) {pyrazolate (Pz(-)), 4-methylpyrazolate (mPz(-)), 3,5-dimethylpyrazolate (dmPz(-)), 4-iodopyrazolate (IPz(-))} have been described in this work. The exobidentate coordination mode of pyrazolato ligands in 1-4 was inferred on basis of IR spectroscopic evidences. TG investigations indicated that the introduction of substituents at the 4 position in the pyrazolyl moiety into coordination polymers do not affect significantly their thermal stability, whereas at the 3 and 5 position reduced the stability of the main chain. Metal palladium was the final product of the thermal decompositions, which was identified by X-ray powder diffraction.
Keywords: coordination polymers; DTA; palladium(II); pyrazolates; TG